Mendidik Karakter Anak melalui Model Pembelajaran Berbasis Proyek (Sebuah Desain Pembelajaran Matematika yang Berkarakter) - Miftha Indasari (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2018)
Character education in the realm of education in elementary school is crucial to be invested because basic education is the beginning of the moral application in human life. In school, children spend their time studying and interacting in their social life. There are several ways in teaching the values of character in school, one of which is to insert the values of characters in the mathematics learning. A real teacher simply directs and creates a learning plan that can accommodate the appearance of the character. One of the learning models that can stimulate the insertion of character values in students is the Project-based Learning model. Thus, the students will learn through the project and indirectly will also emerge the understanding of the character values that exist in the project activities.